Sravnitel'nyj analiz mediko-biologiceskich naucnych issledovanij v dissertacijach v sfere fiziceskoj kul'tury i sporta - Safonov, L. V.; Shustin, B. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The purpose of the research is to evaluate the main directions of modern dissertation research of a medico-biological nature, dedicated to the problems of physical culture and sports. The article analyzes the topics of candidate and doctoral dissertations of medical and biological orientation, devoted to the problems of physical culture and sports for the period 2014-2019. A comparative study of the dynamics of the number of theses defended in recent years, depending on the scientific specialty and their compliance with priority areas of research in the field of physical culture and sports. The distribution of dissertation research on the main groups of sports is considered. There is a clear trend towards a decrease in the total number of dissertations of medical and biological orientation in recent years.